Research trends in library and information science in Argentina during the first decades of the XXI century - Corda, Maria Cecilia; Liberatore, Gustavo (Iberoamerican Journal of Science Measurement and Communication, 2021)
Objective. This paper aims at describing and analyzing the research lines on Library and Information Science (LIS) developed within the institutional framework of the Argentinian universities where careers in Library Science, Archival Science, and Museology are offered. Design/Methodology/Approach. Documents presented at academic events from the Mercosur's schools were gathered, as well as former studies that address the issue. Additionally, the scientific production of researchers and academicians from the LIS field was systematized using the Publish or Perish app, considering Google Scholar as a data source. Results/Discussion. A consolidation of the LIS field was observed, both from the contributions for the conceptual and methodological strengthening of the discipline, and from the inquiries that seek to resolve issues that arise in the professional field of libraries, archives, museums, and other information units. Conclusions. The existence of work lines that combine topics dealt with at an international level in the field was highlighted, as well as areas of specialization, focused on local realities. It was shown that the research development and productivity are concentrated in few schools. Finally, the incipient constitution of postgraduate studies at the specialization, master's degree, and doctorate levels was addressed, which, over time, will broaden the spectrum of research carried out in the universities developing these training sections. Originality/Value. There was no study of this type in which documentary analysis was combined with bibliometrics to reveal researchers, topics, and scientific production in the LIS field in Argentina, something not always easy to capture and address.